INTERLOCKING PLASTIC BLOCK – A REVIEW - Mrs. Sheetal Nalbilwar; Atharva Bhapkar, Karan Patil, Shivraj Jagadale, Krushna Khandare, Sujal Shinde, (EPRA International Journal of Research and Development (IJRD), 2023)
The plastic waste is the hazardous problem in today’s world. This is most dangerous problem in front of World. The most hazardous type of wastes are HDPE and PTE and the plastic below 50micron is also causing a serious problem. This plastic mixed in the soil; it directly effects on fertility of the soil. Nowadays, the large amount of plastic is deposited into sea. This plastic wastes gives hazardous effect on the aquatic life and quality of seawater also polluted by this plastic. So, we try to finding efficient way to solve this problem of plastic waste. So, we added this plastic wastes into the bricks and create the bricks by using plastic wastes. It is most economical solution present in the construction industry and it is also economical and environment friendly solution of the Plastic Wastes. This material is made of a combination of single use plastics mixed with eco-friendly industrial waste. By using these blocks, construction costs are reducing from savings made by the material itself and from labour. Interlocking designs make it easy to build with and requiring less manpower to do so. The same principle can also be used in building sidewalk pavers, interlocking posts, fences and other construction materials.